High temperatures and drought affect the germination of Populus luziarum and P. primaveralepensis, endangered species from the Neotropical region of Mexico - Cesar Jacobo-Pereira; Francisco Martín Huerta-Martínez; Joel Flores; Alvaro Edwin Razo-Leon; Alejandro Muñoz-Urias (Neotropical Biology and Conservation)
The higher temperatures and lower rainfall generated by global warming can have negative repercussions on the physiological responses of plants. This study aims to understand how the higher temperatures and declining precipitation will affect the germination of Populus luziarum and P. primaveralepensis, two endangered endemic species from western Mexico. The germination of these species was evaluated through the combined effect of three temperatures (24, 28, and 32 °C) and five water potentials (0, –0.07, –0.15, –0.3, and –0.6 MPa). The evaluated response variables utilized were the minimum time that seeds need to begin germination, the mean germination rate, and the final percentage of germination. Significant differences were found in the germination of both species due to the factors and their interaction. The highest germination percentages were registered with the combination of 24 °C and 0 MPa for both species (90% and 94%, respectively). The lowest percentage for P. luziarum was recorded at –0.6 MPa for any temperature (26–32%), while the lowest germination (23%) was found for P. primaveralepensis at –0.6 MPa and 32 °C. In addition, germinability was slowest in both species because of the highest temperatures and lowest water potential and their interactions. It is concluded that higher temperatures and drought stress will negatively affect the germination and recovery of populations of these two species.